2014
DOI: 10.1016/j.lssr.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of disseminated intravascular coagulation in a porcine model following radiation exposure

Abstract: Recent evidence has suggested that disseminated intravascular coagulation (DIC) plays an integral role in death at the LD50 dose of either gamma or solar particle event (SPE)-like proton radiation in ferrets. In these studies, Yucatan minipigs were evaluated to determine whether they were susceptible to the development of radiation induced DIC. Yucatan minipigs were exposed to a dose of 2.5 Gray (Gy) with x-rays and monitored over the course of 30 days. Evidence of DIC was evaluated by way of thromboelastometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Though recent attempts to develop the minipig as an animal model for ARS have progressed satisfactorily, the relative radiosensitivity of the Göttingen minipig raises concerns. A recent study suggests that radiation-induced disseminated intravascular coagulation may be a contributing factor to the radiosensitivity of minipigs [19]. Though the referred study has been conducted using X-rays, it is believed that the findings are comparable for X-rays, γ-rays, and solar particle event radiation.…”
Section: Expert Opinionmentioning
confidence: 98%
“…Though recent attempts to develop the minipig as an animal model for ARS have progressed satisfactorily, the relative radiosensitivity of the Göttingen minipig raises concerns. A recent study suggests that radiation-induced disseminated intravascular coagulation may be a contributing factor to the radiosensitivity of minipigs [19]. Though the referred study has been conducted using X-rays, it is believed that the findings are comparable for X-rays, γ-rays, and solar particle event radiation.…”
Section: Expert Opinionmentioning
confidence: 98%
“…Findings from our work indicate that radiation activates the coagulation cascade and induces changes in hemostasis resulting in hemorrhage and RIC. We recently published the results of numerous experiments indicating that radiation exposure can result in bleeding and ultimate death in ferrets and minipigs at doses near the LD 50 ; the evidence suggests that the early changes related to RIC can progress to death resulting from a coagulopathy [(15); reviewed in (6)]. It is expected that changes similar to those observed in ferrets and pigs also occur in other large mammals, including humans, irradiated at or near their respective LD 50 levels (3, 5, 6).…”
Section: Introduction/background Informationmentioning
confidence: 99%
“…Further, it has been recently suggested that the minipig's high radiosensitivity and early death patterns following acute irradiation are not necessarily due to a failure of function of either the hematopoietic or gastrointestinal systems per se, but perhaps mediated largely by DIC. Specifically, recent reports have indeed demonstrated that DIC induced by irradiation may be a promoting factor for the radiosensitivity of minipigs (Krigsfeld et al 2014a(Krigsfeld et al , 2014b. It needs to be noted that the latter study was conducted using an X-ray source and not c-ray source.…”
Section: Discussionmentioning
confidence: 95%
“…disseminated intravascular coagulation (DIC) may be a significant, contributing factor leading to ferret death at the LD 50 dose of radiation (Krigsfeld et al 2014a). DIC is a serious and life-threatening condition in which the coagulation mechanism is over activated, causing bleeding and clotting to occur at the same time (Krigsfeld et al 2014b). This condition may be the major mechanism by which relatively low doses of radiation causes death in large mammals.…”
Section: Ferretmentioning
confidence: 99%
See 1 more Smart Citation